2022
DOI: 10.1097/aud.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Hearing Sensitivity and Different Cognitive Functions with Perception of Speech-in-Noise

Abstract: Objectives: Impaired speech-in-noise perception affects individuals' daily lives and is a frequent symptom of age-related hearing loss, which is a common disabling condition and a health concern in aging populations. The relative impact of hearing sensitivity loss and different cognitive functions on speech-in-noise perception is not well understood. We aimed to assess to what extent hearing sensitivity and different cognitive functions were associated with sentence-in-noise performance across the adult lifesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
(175 reference statements)
0
1
0
Order By: Relevance
“…87 Another study introduced a self-report that considered hearing, vision, cognition and psychosocial functioning on quality of life (hAVICOP) [96]. Merten, et al (2022) [97] found that psychosocial well-being was associated with better hearing, vision, neural and cognitive functioning. Goodwin, Hogervorst and Mairdment (2022) [98] looked at the hearWHO, digits in noise and the Modified Telephone Interview for Cognitive Status (TICS-M) as well as psychosocial well-being and cardiovascular health.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…87 Another study introduced a self-report that considered hearing, vision, cognition and psychosocial functioning on quality of life (hAVICOP) [96]. Merten, et al (2022) [97] found that psychosocial well-being was associated with better hearing, vision, neural and cognitive functioning. Goodwin, Hogervorst and Mairdment (2022) [98] looked at the hearWHO, digits in noise and the Modified Telephone Interview for Cognitive Status (TICS-M) as well as psychosocial well-being and cardiovascular health.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%